Long-term effects of copper nanoparticles on granule-based denitrification systems: Performance, microbial communities, functional genes and sludge properties. (October 2019) - Cheng, Ya-Fei; Zhang, Qian; Li, Gui-Feng; Xue, Yuan; Zheng, Xia-Ping; Cai, Shuang; Zhang, Zheng-Zhe; Jin, Ren-Cun
Graphical abstract: Highlights: The presence of 1 mg L −1 Cu NPs was supposed to be safe in granule-based denitrification systems. The system lost 51.9% of nitrogen removal capacity under the stress of 5 mg L −1 Cu NPs. The presence of 5 mg L −1 Cu NPs reduced the gene abundance of nap A, nar G and nos Z. The introduction of Cu NPs shifted the community composition of denitrifying bacteria. Abstract: The widespread use of copper nanoparticles (CuNPs) has attracted increasing concern because of their potential effects on biological wastewater treatment. However, their effect on granule-based denitrification systems is unclear. Hence, the effects of CuNPs on denitrifying granules were investigated during long-term operation. The results showed that 51.9% of nitrogen removal capacity was lost after exposure to 5 mg L −1 CuNPs, with the amount of Cu(II) gradually increasing with elevating CuNP levels. Moreover, the relative abundance of denitrifying bacteria ( Castellaniella ) and denitrifying functional genes ( nir K, nap A, nar G and nos Z) obviously decreased. Meanwhile, the specific denitrification activity, the content of extracellular polymeric substances and dehydrogenase activity decreased by 44.0%, 15.2% and 99.9%, respectively, compared to their values in the initial sludge. Considering the downtrend in the abundance of copper resistance genes, it was deduced that the toxicity of CuNPs was mainly or at least partially due to the release of Cu(II).